A critical point approach to boundary value problems on the real line. (February 2018) - Bohner, Martin; Caristi, Giuseppe; Heidarkhani, Shapour; Moradi, Shahin
Abstract: We discuss the existence of at least one weak solution for elliptic problems on the real line. Our technical approach is based on variational methods. Some recent results are extended and improved. Examples are presented to demonstrate the application of our main results.